Morphological and microscopic identification studies of Cordyceps and its counterfeits - Hui-juan Liu; Hao-bin Hu; Chu Chu; Qin Li; Ping Li (Acta Pharmaceutica Sinica B, 2011)
Macroscopic and microscopic studies were applied to distinguish Cordyceps sinensis (Berk.) Sacc. and its 5 common counterfeits. Transverse sections of stroma and larvae and surface sections of stroma of C. sinensis, Cordyceps gunnii, Cordyceps barnesii, Cordyceps gracilis, Cordyceps liangshanensis and Cordyceps militaris were examined and their morphological and microscopic features photographed. The main morphological and microscopic features of the 6 species of Cordyceps were basically similar except for certain diagnostic differences. These included macroscopic differences from C. sinensis as follows: the stroma of C. gunnii is stout and rough with sterile bulgy or branched apex; the larvae of C. barnesii has a pair of teeth on the head; the stroma of C. liangshanensi is thread-like; C. gracilis is without stroma; and C. militaris is without larvae. There were also microscopic differences: from C. sinensis as follows: the stroma of C. barnesii is without perithecia; C. gunnii, C. liangshanensis and C. gracilis are without bristles on the larva body. These differences allow C. sinensis and its counterfeits to be easily distinguished.